Measurement of Readiness in IT Adoption Among SMEs Manufacturing Industry in Jakarta. - Asrul, Sani; T.K.A, Rahman; Agus, Budiyantara; Rouly, Doharma (JATIT, 2020)
The development of SMEs, especially those based on the manufacturing industry, is highly developed along with the significant market demand. The increasingly important information technology in SMEs will have an impact on increasing productivity, marketing, and efficiency in this research, measurement of readiness level in the adoption of information technology (IT) will be carried out used to explore the level IT application readiness and to examine factors which influences its application. The survey was conducted on stakeholders of Small and Medium Enterprises in Jakarta, which was done using interview and questionnaire techniques with a response (n = 68). Interviews and questionnaires are conducted on policymakers in SMEs companies so that the data obtained will provide accurate results. Data will be processed using partial least squares structural equation modelling (PLS-SEM) software. The results shown by the majority of respondents (54.4%) answered that the percentage of the level of readiness of SMEs towards IT adoption was more than 50%. Meanwhile, 31.7% of respondents stated that for a percentage of more than 75%. Respondents taken were only about five regions of Jakarta. Also, more comprehensive results will be used as a reference when respondent data will cover all regions of Java. From the results of this study can be used for further research related to the level of readiness for IT adoption in SMEs